Natural Gas Technology - A Correlation of Dewpoint Pressure With Fluid Composition and Temperature - L. K. Nemeth; H. T. Kennedy (The American Institute of Mining, Metallurgical, and Petroleum Engineers)
The investigation presented in this paper was performd to develop a relationship between the dewpoint pressure of a hydrocarbon reservoir fluid and its composition, temperature and characteristics of the heptanes-plus fraction. This is part of an over-all program to develop correlations for the essential properties of reservoir fluids with the composition, temperature and pressure. In all, 579 dewpoint pressures, determined experimentally on 480 different condensate systems along with their compositions and temperatures, were obtained from the literature and from previously unpublished sources. Compositions were expressed in terms of mol fractions of methane through heptanes-plus, nitrogen, carbon dioxide and hydrogen sulfide, and the molecular weight and specific gravity of the heptanes-plus fraction. Distribution of the samples assured a good representation of most of the major oil-producing areas in the world. A multiple regression analysis program written for the IBhl 7094 digital computer was used to compare numerous equations and to calculate their coefficients. The final equation containing 11 coefficients resulted in an average absolute deviation of 7.4 percent for all the samples. Segregation of data on the basis of one or more variables did not materially improve the results. The correlation developed is useful in predicting the dewpoint pressure of condensate reservoir fluids from variables normally measured in the laboratory. INTRODUCTION In any discussion of the dewpoint of hydrocarbon mixtures, it should be noted that there are two kinds of dewpoints which must be distinguished. The first type, or normal dewpoint, usually occurs at low pressures as dry gas is compressed to the point where liquid first forms. The second type, sometimes called the retrograde dewpoint, occurs when a gas mixture containing heavy hydrocarbons in solution is depressured until a liquid is formed. The first type, as applied to condensate mixtures, would normally be below atmospheric pressure and would be of no interest in reservoir performance. The second type is of great significance in interpreting reservoir behavior and is the property referred to throughout this paper. Laboratory measurement of dewpoints is laborious, expensive and subject to many errors, and it is desirable to find a reasonably accurate method to predict dewpoint pressures from the composition and other readily available properties normally measured on the fluids. A possible method of calculating dewpoint pressures would be to employ a set of equilibrium ratios (K-values). 1 However, the K-values themselves depend on composition as well as temperature and pressure; presently their use adds nothing to the accuracy of predicting dewpoints. If future correlations provide a significantly better method of estimating K-values for heavy hydrocarbons, they may be of greater use. REVIEW OF LITERATURE In 1944, Olds, Sage and Lacey 2 studied the behavior of fluids from the Paloma field. Properties of seven mixtures were studied at temperatures ranging from 100 to 250 F and at pressures up to 5,000 psia. From the information obtained, the influence of composition and temperature upon the dewpoint was determined. It was found that removal of the intermediate molecular weight components from the mixture resulted in considerable increases in the dewpoint pressures. Results indicated that the effect of changes in temperature was relatively minor when compared with the effect of modifying the mixture by removing the intermediate components. Thus, removal of propane and butanes resulted in an increase in dewpoint pressure more than 10 times greater than a change in temperature from 100 to 250 F. The authors stated that althouah